Lifestyle mobilities intersections of travel, leisure and migration - Duncan, Tara; Cohen, Scott A.; Thulemark, Maria (Current developments in the geographis of leisure and tourism, 2013)
Being mobile in today's world is influenced by many aspects including transnational ties, increased ease of access to transport, growing accessibility to technology, knowledge and information and changing socio-cultural outlooks and values. Bringing together scholars from geography, sociology, tourism, history and beyond.